Bibliometric Mapping of Scientific Production and Conceptual Structure of Cyber Sextortion in Cybersecurity - Fani Moses Radebe; Kennedy Njenga (Social Sciences)
This study examines cyber sextortion research using a comprehensive bibliometric analysis. In the field of cybersecurity, cyber sextortion is a form of cybercrime that leverages privacy violations to exploit a victim. This study reviewed research developments on cyber sextortion progressively over time by looking at scientific productions, thematic developments, scholars’ contributions, and the future thematic trajectory. A bibliometric approach to analyzing the data was applied, which covered 548 peer-reviewed articles, conference papers, and book chapters retrieved from the Scopus database. Results showed a growth trajectory on various thematic concerns in the cyber sextortion field, which has continued to gain traction since the year 2023. Notably, online child sexual abuse is a growing theme in cyber sextortion research. In addition, among other themes, adolescents, mental health, and dating violence are receiving interest among scholars in this field. Additionally, institutions and prolific scholars from countries such as the United States of America, Australia, and the United Kingdom have established research collaborations to improve understanding in this field. The results also showed that research is observed to be emerging from South Africa and Ghana in the African region. Overall, there is potential for more scientific publications and researchers from Africa to contribute to this growing field. The value this study holds is moving beyond deficit-based approaches to how adolescent youth can be resilient and protected from cyber sextortion. A call for a multidisciplinary approach that moves beyond deficit-based approaches toward resilient and autonomy-based approaches is encouraged so that adolescent youth are protected from exploitation. This approach should focus on investigating proactive and resilience-based interventions informed by individuals’ traits and contexts to aid in building digital resilience in adolescents.